UJI KUALITAS MIKROBIOLOGI DAN KIMIAWI SEDIAAN YOGHURT BERBAHAN DASAR KACANG BOGOR (Vigna subterranea) - Rika Sri Agustina; Tri Saptari Haryani; . Ismanto (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2021)
Yogurt is milk fermented with Lactobacillus bulgaricus and Streptococcus thermophilus bacteria. Yoghurt is derived from milk, which is a source of protein, one source of vegetable protein is bambara groundnut milk. The purposes of this research are to determine the quality of yoghurt made from bambara groundnut through microbiological and chemical tests and to determine the concentration of milk and the optimal fermentation temperature for making yoghurt with the best quality. This research used a completely randomized factorial design with the concentration of bambara groundnut milk of 15%, 20%, and 25% and the fermentation temperature of 35°C, 40°C, and 45°C and a four-time repetition. The result of this research shows that the best quality of yoghurt made from bambara groundnut was obtained from the treatment of bambara groundnut milk with the concentration of 20% and the fermentation temperature of 45°C with the results of total coliform, Salmonella sp., Listeria monocytogenes, total lactic acid bacteria, bacterial morphology, protein, acidity, fat and organoleptic respectively: 0 MPN/gram, negative/25gram, negative/25gram, 2.6x109 colonies/gram, circular shape, milky white, convex elevation, Gram positive, 3.74%, 1.77 %, 0.68% and liked by panelists.